Coping strategies of elite Hungarian junior handball players - Ökrös, C.; Konig-Görögh, D.; Gyömbér, N. (Acta Medicinae Et Sociologica, 2020)
Several studies provided instruments, with the possibility to measure self-assessment and coping strategies. This study aimed to study differences in coping strategies by age groups and gender in handball players. For psychological profile the Athletic Coping Skills Inventory (ACSI-28) was applied, at elite Hungarian junior handball teams (n=288) in 2016-2017. On the scales Coping with Adversity and Freedom From worry males acquired significantly higher average values, females showed higher mean values of Goal Setting/Mental Preparation and Coachability. On Freedom from Worry, the oldest players performed the best, Coachability was highest in the youngest group. High values of Concentration were measured by playmakers, which was significantly higher than that of other offensive roles. With the results of our study, we would like to draw attention to the fact that for successful preparation, the knowledge of the athlete's coping skills and theirself - knowledge are in dispensable.